Reliability and Validity of RIASEC Holland’s on Predicting Success Career for Vocational Students - Thamrin, Thamrin; Giatman, Giatman; Syah, Nuhasan (Jurnal Kependidikan, 2023)
This study aims to test the reliability and construct validity of the Holland RIASEC instrument, which is a psychometric approach to examining human personality based on six domains, namely Realistic, Investigative, Artistic, Social, Enterprising, and Conventional. This instrument is used to measure and recommend the type of work that suits studentsâ€™ personalities in the vocational field.Â This study uses a non-experimental method with a quantitative research approach and involved 178 vocational students at Universitas Negeri Padang. The data analysis techniques used are Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA). The results showed that the reliability of the six Indonesian version of Hollandâ€™s personality was quite high, with Cronbachâ€™s alpha values between 0.601 and 0.699. In addition, there was a positive correlation between Hollandâ€™s personality. Construct validity showed a fit model with a p-value of 0.26972 and RMSEA = 0.02. This indicates that the empirical data is in line with the RIASEC typology model, which is the theoretical concept.